The Impact of Ethical Behavior and Facets of Job Satisfaction on Organizational Commitment of Chinese Employees - Fu, Weihui; Deshpande, Satish P.; Xiao, Zhao (2011)
This study examines factors impacting organizational commitment of 214 employees working at a Chinese state-owned steel company. Ethical behavior of peers and ethical behavior of successful managers had a significant impact on organizational commitment. The four facets of job satisfaction (pay, coworker, supervision, and work itself) had a significant impact on organizational commitment. Respondent’s age also significantly impacted organizational commitment. Perceptions of ethical behavior of successful managers, satisfaction with work, and gender were significantly correlated with social desirability bias.
Keywords: Steel company; Organizational Commitment; Job satisfaction; Ethical Behavior; China